Development and Validation of Animation-Based Science Learning Media in the STEM-PBL Model to Improve Students Critical Thinking and Digital Literacy - Fitria Lafifa; Dadan Rosana (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to produce an animation technology-based learning media product with the STEM-PBL model to improve critical thinking and digital literacy that is feasible and valid. The research uses a 4-D model. The research subjects were 27 MTsN, 1 Blitar City student, two expert lecturers, and one science teacher. The instruments used were validation sheets, readability, and practicality questionnaires with a 5-level Likert scale. The data analysis technique is descriptive and uses the ideal standard deviation value. The research results show that the product is in a very valid and feasible category, with a percentage of 94% material experts and 92% media experts. The readability and practicality tests are in a very good variety with rates of 85% and 99%. So that the product is very feasible and valid to use in learning. The recommendation for further research is to test the effectiveness of media when learning to improve student's critical thinking and digital literacy.